Assessment of the Effects of Enamel Remineralization After Treatment with Hydroxylapatite Active Substance: SEM Study - Marcella Reguzzoni; Andrea Carganico; Doriana Lo Presti; Piero Antonio Zecca; Eleonora Ivonne Scurati; Margherita Caccia; Luca Levrini (Applied Sciences)
This study aimed to investigate the remineralization processes of dental enamel via scanning electron microscopy and observe the changes induced in the microstructure by oral hygiene products. More specifically, the effectiveness of Mentadent Professional Resilience was analyzed for its ability to demineralize erosion-affected enamel surfaces. This involved the sectioning of some teeth to preserve enamel integrity, followed by dehydration and preparation for SEM analysis. SEM observations were made at various magnifications to detect differences in enamel morphology after treatment with the product. These observations provide valuable insights into the mechanisms of action of dental care products and their potential to protect enamel. The study makes a contribution to our understanding of remineralization processes and describes the importance of microscopic analysis for evaluating and developing effective dental products.